Spectroscopic studies of iron-based SCR catalysts -Investigation of thermal deactivation processes - Adams, Emma (My University, 2012)
The thermal stability of iron/beta (Fe/BEA) as an SCR catalyst was studied. Samples were treated in the absence of water at 700, 800 and 900°C for 6 to 48 hours and characterized by nitrogen physisorption and UV-vis spectroscopy. DRIFT spectroscopy was also used, not only to characterize the Fe species present, but also to correlate any changes in activity with changes in iron and/or zeolite structure. Deconvolution of the UV-vis spectra showed an increase in the production of small clusters and larger surface particles with ageing time and temperature, with a subsequent reduction of isolated Fe2+ and Fe3+ ions. These results were in correlation with the NO temperature programmed desorption results of the DRIFTS experiments. Ageing for extended periods of time and/or temperature resulted in a decrease in surface area of the zeolite and eventually zeolite collapse. This could be correlated to the reduction in Brønsted acid sites as found by the NH3 temperature programmed desorption results of the DRIFTS experiments and is responsible for the reduction in ammonia adsorption capacity with ageing.
Keywords: Spektroskopi; Energi; Grundläggande vetenskaper; Hållbar utveckling; Katalys; Materialvetenskap; Nanovetenskap och nanoteknik; Transport; Spectroscopy; Energy; Basic Sciences; Sustainable Development; Catalysis; Materials Science; Nanoscience & Nanotechnology; Transport